Psychosocial Correlates of Young Females Suffering from Polycystic Ovarian Syndrome (PCOS) - Rafique, Saher; Ilyas, Uzma (Pakistan Armed Forces Medical Journal, 2022)
Objective: To explore the psychosocial correlates of women under treatment for polycystic ovarian syndrome (PCOS).Study Design: Cross sectional study.Place and Duration of Study: Different Clinics and Hospitals of Lahore and Gujranwala, from Aug 2019 to Nov 2020.Methodology: Single women seeking treatment for PCOS were included in the study. Derriford appearance scale and social interaction anxiety scale were used in this study.Results: A total of 180 women were included in the study. The result indicated significant positive correlation between appearance distress and social anxiety (r=0.41, p